The lost peace : leadership in a time of horror and hope, 1945-1953 - Dallek, Robert (New York : Harper, 2010)
In a reinterpretation of the postwar years, historian Robert Dallek examines what drove the leaders of the most powerful nations around the globe--Roosevelt, Churchill, Stalin, Mao, de Gaulle, and Truman--to rely on traditional power politics despite the catastrophic violence their nations had endured. The decisions of these men, for better and often for worse, had profound consequences for decades to come, influencing relations and conflicts with China, Korea, the Middle East, and around the globe. This book is a penetrating look at the misjudgments that caused enormous strife and suffering during this critical period, from the closing months of World War II through the early years of the Cold War. The men who led the world at this time executed astonishingly unwise actions that propelled the nuclear arms race and extended the Cold War. Dallek has written a cautionary tale that considers what might have been done differently.--From publisher description.
London, Moscow , and Washington: friends in need -- From Tehran to Roosevelt's death -- Collapse and renewal -- Hope and despair -- Irrepressible conflicts? -- The triumph of fear -- Cold war illusions-and realities -- War by other means -- The military solution -- Limited war -- Elusive peace.
Includes bibliographical references (p. [395]-400) and index.
Keywords: World politics -- 1945-1955.; World War, 1939-1945 -- Peace; Cold War